The combination of obesity and hypertension: a highly unfavorable phenotype requiring attention. (July 2016) - Arena, Ross; Daugherty, John; Bond, Samantha; Lavie, Carl J.; Phillips, Shane; Borghi-Silva, Audrey
Abstract : Purpose of review: Body habitus is a key lifestyle characteristic whose current status and future projections are disconcerting. The percentage of the global population who are either overweight or obese has substantially increased, with no indication that any country has a solution to this issue. Hypertension is a key unfavorable health metric that, like obesity, has disastrous health implications if left uncontrolled. Poor lifestyle characteristics and health metrics often cluster together to create complex and difficult to treat phenotypes. Excess body mass is such an example, creating an obesity–hypertension phenotype, which is the focus of this review. Recent findings: An increased risk for hypertension is clearly linked to obesity, indicating that the two conditions are intimately linked. The cascade of obesity-induced pathophysiologic adaptations creates a clear path to hypertension. Adopting a healthy lifestyle is a primary intervention for the prevention as well as treatment of the obesity–hypertension phenotype. Summary: The obesity–hypertension phenotype is highly prevalent and has disastrous health implications. A primordial prevention strategy, focused on lifelong healthy lifestyle patterns, is the optimal approach for this condition. For those individuals already afflicted by the obesity–hypertension phenotype, interventions must aggressively focus on weight loss and blood pressure control.